Arthrogenic muscle response to a simulated ankle joint effusion. Issue 1 (29th January 2004) - Palmieri, R M; Ingersoll, C D; Hoffman, M A; Cordova, M L; Porter, D A; Edwards, J E; Babington, J P; Krause, B A; Stone, M B
Abstract : Background: Arthrogenic muscle inhibition (AMI) is a continuing reflex reaction of the musculature surrounding a joint after distension or damage to the structures of that joint. This phenomenon has been well documented after knee joint injury and has been generalised to occur at other joints of the human body, yet minimal research has been conducted in this regard. The response of the muscles crossing the ankle/foot complex after ankle injury and effusion is not well understood. AMI may occur after an ankle sprain contributing to residual dysfunction. Objective: To determine if AMI is present in the soleus, peroneus longus, and tibialis anterior musculature after a simulated ankle joint effusion. Methods: Eight neurologically sound volunteers (mean (SD) age 23 (4) years, height 171 (6) cm, mass 73 (10) kg) participated. Maximum H-reflex and maximum M-wave measurements were collected using surface electromyography after delivery of a percutaneous stimulus to the sciatic nerve before its bifurcation into the common peroneal and posterior tibial nerves. Results: The H-reflex and M-wave measurements in all muscles increased (p⩽0.05) after the simulated ankle joint effusion. Conclusions: Simulated ankle joint effusion results in facilitation of the soleus, peroneus longus, and tibialis anterior motoneurone pools. This may occur to stabilise the foot/ankle complex in order to maintain posture and/or locomotion.